Provider Perspectives of Battlefield Acupuncture: Advantages, Disadvantages and Its Potential Role in Reducing Opioid Use for Pain. Issue 9 (September 2020) - Giannitrapani, Karleen F.; Ackland, Princess E.; Holliday, Jesse; Zeliadt, Steve; Olson, Juli; Kligler, Benjamin; Taylor, Stephanie L.
Abstract : Objectives: Nonpharmacological options to treat pain are in demand, in part to address the opioid crisis. One such option is acupuncture. Battlefield acupuncture (BFA) is an auricular needling protocol currently used to treat pain in the Veterans Health Administration. We aimed to identify the advantages and disadvantages of BFA from providers' perspectives. Methods: We rely on an inductive qualitative approach to explore provider perceptions through thematic analysis of semistructured interviews with 43 BFA providers across the nation. Results: We identified the following themes. Disadvantages included: (1) clinical guidelines are insufficient; (2) patients often request multiple BFA visits from providers; (3) BFA can be uncomfortable; (4) BFA may not be an effective treatment option unless it can be provided "on demand"; and (5) BFA can promote euphoria, which can have deleterious consequences for patient self-care. Perceived advantages included: (1) BFA can simultaneously effectively control pain while reducing opioid use; (2) BFA may alleviate the pain that has been unsuccessfully treated by conventional methods; (3) BFA gives providers a treatment option to offer patients with substance use disorder; (4) BFA helps build a trusting patient-provider relationship; (5) BFA can create the opportunity for hope. Conclusions: Providers perceive BFA to have many benefits, both clinical and relational, including ways in which it may have utility in addressing the current opioid crisis. BFA is easy to deliver and has potential clinical and relational utility. Efforts to better understand effectiveness are warranted.